Self-assembled FePt nanocrystals with large coercivity: Reduction of the fcc-to-L1(0) ordering temperature - Varanda, Laudemir Carlos; Jafelicci, Miguel (Amer Chemical Soc, 2006)
Herein we report the synthesis and properties of Fe55Pt45 nanoparticles, both monodisperse and self-assembled into hexagonal close-packed and cubic arrays of 4.0 +/- 0.2 nm size in an L1(0) structure, obtained by a modified polyol process. The new synthetic route improved the control over the particle composition, thereby reducing the temperature required to convert from face-centered cubic (fcc) to face-centered tetragonal (fct) phase by some 30-50 degrees C without additives. Annealing at 550 degrees C for 30 min converts the self-assembled nanoparticles into ferromagnetic nanocrystals with large coercivity, H-C = 11.1 kOe. Reducing the fcc-to-fct (L1(0)) ordering temperature avoided particle coalescence and decreased the loss in particle positional order without compromising the magnetic properties, as is generally observed when additives are used.